2017
DOI: 10.1155/2017/9867694
|View full text |Cite
|
Sign up to set email alerts
|

Can the Weight of an External Breast Prosthesis Influence Trunk Biomechanics during Functional Movement in Postmastectomy Women?

Abstract: Introduction Recent papers indicate that one-side mastectomy can produce deleterious effects on the posture and musculoskeletal system. This study was conducted to better understand the underlying mechanisms involved in trunk motion in external prosthesis users. Objective The aim was to evaluate the changes in surface electromyographic (SEMG) activity of the erector spinae muscles (ES) in postmastectomy women with and without breast prostheses during functional body movement tests. Methods In 51 one-side postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Hojan & Manikowska reported that the weight of the external breast prosthesis did not affect the activities of LES during dynamic state at after mastectomy (21). In our study, muscular activities were significantly lower in bilateral TES in the Rt.…”
Section: Discussioncontrasting
confidence: 40%
“…Hojan & Manikowska reported that the weight of the external breast prosthesis did not affect the activities of LES during dynamic state at after mastectomy (21). In our study, muscular activities were significantly lower in bilateral TES in the Rt.…”
Section: Discussioncontrasting
confidence: 40%
“…Recent articles indicate that one-sided mastectomy or minor breast surgery to treat breast cancer can have deleterious effects on posture and the musculoskeletal system such as alterations in spine alignment, an increased thoracic kyphosis and upper limb dysfunctions, and decrease of shoulder joint angles at the operated side, 4 but other studies appear to contradict these statements. 1,5 After breast cancer surgery, patients have reduced physical participation in valuable activities contributed, more specifically, to explaining variability in depression. 6 The patient tends to assume an attitude of closure, especially versus the presurgery “protective posture.” In the early stages after surgery, this attitude is also due to modesty and shyness.…”
Section: Introductionmentioning
confidence: 99%
“…The question whether EBP influences the postural stability of women who underwent mastectomy was not answered by the previous studies. Moreover, the literature on the subject indicates that the EBP does not play such a significant role as it could be assumed in the postural control of women who underwent unilateral mastectomy ( 11 , 28 , 30 ). Karczewska et al., based on studies assessing the influence of external prostheses on the dynamic balance of women who underwent unilateral mastectomy, found that the breast prosthesis did not affect the quality of equivalent reactions in the dynamic study ( 24 ).…”
Section: Discussionmentioning
confidence: 99%